2018
DOI: 10.2478/bog-2018-0028
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Communications, physical distance and access to follow-up healthcare service in Lagos Metropolis

Abstract: The widespread use of mobile communications has resulted in a new practice in family and social life, with significant implications for physical distance. This is because mobile communication allows users to overcome spatial issues such as distance to healthcare services, shift to person-to-person connectivity, and the blur boundaries between one point and another. The uneven distribution of healthcare facilities and distances among them has compounded the provision of follow-up care services to healthcare see… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…When a physical, in-person follow-up is not possible, remote patient assessment via phone or other communication technologies could serve as a viable alternative (28,29). The COVID-19 pandemic resulted in the expanded use of telemedicine and other technologies to deliver healthcare services in Uganda (30).…”
Section: Discussionmentioning
confidence: 99%
“…When a physical, in-person follow-up is not possible, remote patient assessment via phone or other communication technologies could serve as a viable alternative (28,29). The COVID-19 pandemic resulted in the expanded use of telemedicine and other technologies to deliver healthcare services in Uganda (30).…”
Section: Discussionmentioning
confidence: 99%
“…As referral centers, patients patronize the centers from the Lagos metropolis and neighboring towns. Similarly, a survey conducted at one of the participating institutions revealed that more than half of the patients patronizing the facility come from distances longer than 10 km [ 44 ]. Similarly, the survey revealed that about 44.4% of the patients resided outside the Lagos metropolis, thus increasing mobile phone usage among patients [ 44 ].…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, a survey conducted at one of the participating institutions revealed that more than half of the patients patronizing the facility come from distances longer than 10 km [ 44 ]. Similarly, the survey revealed that about 44.4% of the patients resided outside the Lagos metropolis, thus increasing mobile phone usage among patients [ 44 ]. Getting to the institutions is also stressful for the patients, as a study revealed that an average commuter in Lagos spends 2.21 h per day getting to work due to traffic congestion [ 45 ].…”
Section: Methodsmentioning
confidence: 99%